2005
DOI: 10.1523/jneurosci.1306-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Cerebral Microvascular Amyloid-β Protein Deposition Diminishes Regional Neuroinflammation in Vasculotropic Mutant Amyloid Precursor Protein Transgenic Mice

Abstract: Cerebral microvascular amyloid-␤ (A␤) protein deposition is emerging as an important contributory factor to neuroinflammation and dementia in Alzheimer's disease and related familial cerebral amyloid angiopathy disorders. In particular, cerebral microvascular amyloid deposition, but not parenchymal amyloid, is more often correlated with dementia. Recently, we generated transgenic mice (Tg-SwDI) expressing the vasculotropic Dutch (E693Q)/Iowa (D694N) mutant human A␤ precursor protein in brain that accumulate ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 42 publications
6
50
0
Order By: Relevance
“…For example, previous work in human A␤PP transgenic mice showed that the absence of endogenous mouse ApoE strongly reduced the deposition of normal human A␤ in the CNS (Bales et al, 1999;Holtzman, 2001Holtzman, , 2004Fryer et al, 2003). Similarly, we found that the lack of endogenous mouse ApoE prevented Dutch/Iowa CAA mutant cerebral microvascular amyloid accumulation and primarily reduced parenchymal diffuse A␤ deposits in Tg-SwDI mice (Miao et al, 2005b). Furthermore, in this study, we showed that the strong reduction of fibrillar cerebral microvascular A␤ deposition in Tg-SwDI mice decreases microvascular amyloid-induced neuroinflammation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For example, previous work in human A␤PP transgenic mice showed that the absence of endogenous mouse ApoE strongly reduced the deposition of normal human A␤ in the CNS (Bales et al, 1999;Holtzman, 2001Holtzman, , 2004Fryer et al, 2003). Similarly, we found that the lack of endogenous mouse ApoE prevented Dutch/Iowa CAA mutant cerebral microvascular amyloid accumulation and primarily reduced parenchymal diffuse A␤ deposits in Tg-SwDI mice (Miao et al, 2005b). Furthermore, in this study, we showed that the strong reduction of fibrillar cerebral microvascular A␤ deposition in Tg-SwDI mice decreases microvascular amyloid-induced neuroinflammation.…”
Section: Discussionsupporting
confidence: 80%
“…The finding that Tg-SwDI mice accumulate extensive cerebral microvascular A␤, despite low levels of transgene-directed human A␤PP expression, appears to primarily result from ineffective clearance of Dutch/Iowa mutant A␤ from brain across the blood-brain barrier into the circulation (Davis et al, , 2006Deane et al, 2004). In Tg-SwDI mice, cerebral microvascular amyloid deposition is intimately linked with a robust neuroinflammatory response, highlighted by localized strong microglial activation and deficits in spatial learning and memory (Miao et al, 2005b;Fan et al, 2007;Xu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…5A). To compare APPsw͞NOS2 Ϫ/Ϫ with APPsw littermates, we directly measured soluble and insoluble A␤40 and A␤42 levels in brain lysates by using a quantitative ELISA (19,20). Total brain A␤ levels were significantly greater in APPsw͞NOS2 Ϫ/Ϫ mice compared with APPsw littermate controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Soluble and insoluble pools of A␤40 and A␤42 were measured with a specific ELISA and differential brain extractions as described (19,20).…”
Section: Methodsmentioning
confidence: 99%
“…Derived from the amyloid protein precursor, Aβ aggregates in plaques in the brain and in cerebral vessels are a diagnostic feature of AD [37]. Aβ deposited in plaques in the walls of cerebral blood vessels causes cerebral amyloid angiopathy (CAA) [100], and is available to bind to circulating cells including erythrocytes [65,71,76]. Amyloid deposits in cerebral vessels can obliterate the lumens of cerebral arteries and damage the endothelium and basal lamina, causing a breakdown of the blood brain barrier (BBB), ischemia, and neurodegeneration [51,71,102].…”
Section: Aβ and Cerebral Amyloid Angiopathymentioning
confidence: 99%